Metabolism of the novel Ca2+-mobilizing messenger nicotinic acid-adenine dinucleotide phosphate via a 2'-specific Ca2+-dependent phosphatase. - Berridge, G; Cramer, R; Galione, A; Patel, S (2002)
Nicotinic acid-adenine dinucleotide phosphate (NAADP) is a newly described Ca2+-mobilizing nucleotide that appears to target intracellular Ca2+-release channels distinct from those sensitive to inositol trisphosphate or ryanodine/cyclic ADP-ribose. Little, however, is known concerning the regulation of cellular NAADP levels. In the present study, we have characterized the metabolism of NAADP by brain membranes. From HPLC and MS analyses we show that loss of NAADP was associated with the appearance of a major product that is likely to be nicotinic acid-adenine dinucleotide (NAAD), the dephosphorylated form of NAADP. Dephosphorylation of NAADP, but not 3'-NAADP, was dramatically attenuated by Ca2+ chelators and stimulated by Ca2+ over a physiological range in a calmodulin-insensitive manner. In contrast, NADP was metabolized predominantly to ADP-ribose phosphate via glycohydrolase activity, although slower Ca2+-dependent dephosphorylation of both NADP and 2'-AMP could also be demonstrated. This is the first report describing a Ca2+-regulated 2'-specific phosphatase which is probably the major pathway for the inactivation of NAADP in brain. Our data provide a potential feedback mechanism for limiting NAADP-induced Ca2+ release within cells through stimulation of NAADP metabolism by Ca2+ and strongly support a signalling role for this novel nucleotide in the brain.